HEALING ENVIRONMENT CONCEPT APPLYING A SEQUENCE AS AN APPROACH TO MEDAN MEDITATION CENTER DESIGN - Harisdani, Devin Defriza; Avira, Jihan Nafa (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2024)
Mental or mental health is an important aspect in realizing a person's overall health. For this reason, mental health needs to be considered like physical health, because indirectly mental health that is not well maintained also affects the decline in physical health. A person must be free from mental problems so that he can gain well-being in life. In Indonesia, there are a number of problems that arise and have the potential to trigger mental health problems. A person who lives in an urban area tends to experience stress both caused by the demands of work and the consequences of environmental pressure. Many urban residents experience stress due to limited public space, such as one of which occurred in the city of Medan. One problem as an example that is very visible and often occurs is the problem of congestion and the situation in the city of Medan. Nowadays meditation is no longer represented only in a spiritual context. Positive support from the surrounding environment is very influential in maintaining a person's mental health. The design of the meditation building is located on Jalan Flamboyan II, Simpang Selayang, Medan Tuntungan, Medan City. In the design process, the meditation building will be connected to this elite area and designed to combine the concept of healing environment with the sequence in the architecture.